Research’s policies on health: fundamental texts of the European Union and Greece - Masoura, Photini; Skitsou, Alexandra; Laizinou, Alexandra-Nektaria; Charalambous, George (Health & Research Journal, 2023)
The research on health has to offer new data which are based on empirical facts. That fact doesn’t make the research immoral or without limits. The purpose of this study is the survey of the existing knowledge about the scientific research on the health’s field and the promotion of the major institutional legislation that set the boundaries of the research as well as of the problems that arise from it. We noticed a lack of published articles about the European policies around research on health. We present new data and we ended up to conclusions which for the first time are been published in this domain. Main aim is to expand the policies that the European Union follows on the field of health’s scientific research that come up through studying relevant legislation. We studied the main international and European institutional and legislative articles as well as Greek domestic law through Google scholar and the website (of) World Medical Association , through the Greece’s National printing house , the Greek parliament, the European council and the European’s Commission’s site that sets the boundaries of the scientific study on the health’s field and we proceed on a historical flashback so we would be able to explain the need of the creation of these legislative texts. The research took place in December of 2017 and it got repeated in March-April of 2021. The medical research was originally aiming the improvement of the human life. In the legislative texts which try to put restrictions in the ways of the scientific research’s conduction, there are some gaps. New forms of scientific research create some questions considering the subject’s safety. In conclusion several concerns came up which demand to be answered with insight and creative thought.